Community Building of Putra Puspita Youth Organization in Creating Youth Employment in Kutukulon Village - Ridho, Irvan Nur; Triono, Bambang; Pinaryo, Pinaryo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research aimed to understand how the community building model has been implemented through the establishment and growth of institutions and the creation of the BUMDes village community. The research method used was library research, which involved obtaining data and information using a variety of library materials, including reference books, previous study findings on the same topic, articles, notes, and various journals relevant to the issue. Research findings suggested that providing template training in the Kutukulon Village could inspire participants to pursue their own entrepreneurial endeavors. As a result, training programs not only provide skills but also provide targeted support with low-income community involvement. The social prosperity that could reduce the social inequalities and imbalances of the community that was basically a young man from the village of Kutukulon who was able to control the issues of social welfare makes this activity a guideline for the growth of society